Eksekusi Pidana Pembayaran Ganti Kerugian dalam Kasus Tindak Pidana Korupsi (Studi Kasus di Kejaksaan Negeri Surakarta) - Nugroho, Topik Adi; , H. Hartanto, S.H., M.Hum; , Muchamad Iksan, S.H., M.H (2015)
This study aimed to describe the role and constraints Surakarta State Attorney in the criminal execution payment of compensation in cases of corruption. The method used is empirical juridical approach that is descriptive. Types and sources of data comprising primary and secondary data is literature study and interviews. Data were collected through library research and interview, and then analyzed by qualitative analysis method. The results showed Role of Prosecutors in implementing the court decision on criminal execution payment of compensation in cases of corruption that have legal force continues to run well. This is based on the task of Attorney as executor for execution in accordance with the rules of the existing legislation. Treasure / or confiscated assets belonging to the convicted person then submitted to KPKNL to do an auction where the proceeds of the auction are used to cover the financial loss to the state. Regarding obstacles State Attorney Surakarta in executions payment of compensation in cases of corruption, there are actually no barriers faced by the public prosecutor in the State Attorney Surakarta in executions payment of compensation in cases of corruption, particularly related to the execution of the auction in order to pay compensation state finances. This can happen in general convicted person has paid the state financial losses prior to read out their demands, so during the investigation process in the prosecution of the accused are already returning results Attorney corruption is the country's financial losses.